Impact Assessment of China-India Strategic Competition on Security Dynamics of South Asia - Saira Rehman (CISS Insight Journal, 2024)
The politics of South Asia predominantly revolves around two major players in the region: China and India. The emergence of China as a global power in the realm of geopolitics and geo-economics has directly impacted the power dynamics of South Asia. China and India have become competitive states, primarily due to the overarching interdependent linkages that integrate various world regions. This competition is further intensified by focused economic and regional connectivity projects, particularly under China’s Belt and Road Initiative (BRI). China is influencing intraregional dynamics by expanding its political, financial, and security ties with smaller South Asian states. China’s increased engagement in the region has provoked pushback from India, which has traditionally viewed South Asia as its natural sphere of influence. This intensifying competition between the two Asian powers has significant implications for South Asia’s security and economic development, as their geostrategic interests increasingly overlap. Meanwhile, the smaller South Asian states are carefully maneuvering between these competing powers to maximize their political and financial benefits. This study examines the emerging trends in South Asia, driven by the strategic maneuvering of China and India, and the shifting regional dynamics impacting peace and stability in the region. The central question explored in this paper is how the smaller states of South Asia are navigating their national interests while being caught between the two regional giants i.e., China and India. The paper finds that despite China’s economic rise and India’s ambitions for great power status, South Asia is unlikely to become a theater of bloc politics.